Utilizing Topical Therapies and Mitomycin to Reduce Scars - Cupp, Craig; Gaball, Curtis Wesley (Facial Plastic Surgery, 2012)
Minimizing scar size, width, and contour of elevation is a common goal for the facial plastic surgeon. Various standard techniques are employed to reduce tension and enhance the rapid and uneventful healing of incisions. In some cases, these routine measures are not judged to be adequate, and additional intraoperative and postsurgical measures are employed to control the body's innate healing processes. Mitomycin C and self-drying silicone gel have been particularity useful in our practice.
Keywords: scar; mitomycin C; keloid